Caracterização microestrutural do aço duplex UNS S32750 nitretado a baixa temperatura com baixa potência de plasma - Durand, Lucas Tomazi (2020)
Low-temperature nitriding of stainless steels is a treatment that has been widely studied in recent years, however, few studies have been dedicated to its application in duplex stainless steels. Among the main researches, divergences of results have been obtained regarding the nitrided layer structure: expanded austenite formation on both phases; expanded austenite with the presence of nitrides; expanded austenite and ferrite; and compound layer. In order to better understand the structure of the nitrided layer, this work aims to study the microstructure of UNS S32750 duplex stainless steel after nitriding with auxiliary heating under different time and temperature conditions, namely: 300ºC for 4h; 350° C for 2 h; 350° C for 4 h; 350° C for 8 h; and 400ºC for 4 h, and the evolution of nitrogen content and microstructure with heating after nitriding. For this, samples of this material were produced and nitrided, and characterizations such as scanning microscopy (SEM), X-ray wavelength dispersive spectroscopy (WDS), X-ray diffraction (XRD) and instrumented indentation were performed to evaluate formed layer and its characteristics. In order to verify the evolution of the nitrogen content and phases of the formed layer, three selected samples were heated, with simultaneous X-ray diffraction performed at the Brazilian Synchrotron Light Laboratory (LNLS). The results revealed the presence of an expanded austenite monophasic layer over both phases of the material, without the presence of chromium nitrides. The thickness of these layers, however, was small due to the low applied plasma power (15 W), in order to allow resistive heating influence. Nevertheless, high levels of nitrogen were measured in the layer, from 8.62% in austenite and 3.61% in ferrite of the nitrided sample at 350ºC / 2 h, up to 14.72% in austenite and 15.53% in ferrite. Nitrided sample at 350ºC / 8 h (mass contents), which are related to the hardness data obtained, só that the highest hardness was found in the material most enriched with nitrogen. The heating of the samples revealed that only the samples with higher nitrogen concentration expanded austenite decomposes in chromium nitrides, in addition to the diffusion of nitrogen into the sample, causing the layer thickness to increase.